A Seismic Isolation Application Using Rubber Bearings; Hangar Project in Turkey - Sesigur, Haluk; Cili, Feridun; Santini, Adolfo; Moraci, Nicola (AIP, 2008)
Seismic isolation is an effective design strategy to mitigate the seismic hazard wherein the structure and its contents are protected from the damaging effects of an earthquake. This paper presents the Hangar Project in Sabiha Gokcen Airport which is located in Istanbul, Turkey. Seismic isolation system where the isolation layer arranged at the top of the columns is selected. The seismic hazard analysis, superstructure design, isolator design and testing were based on the Uniform Building Code (1997) and met all requirements of the Turkish Earthquake Code (2007). The substructure which has the steel vertical trusses on facades and RC H shaped columns in the middle axis of the building was designed with an R factor limited to 2.0 in accordance with Turkish Earthquake Code. In order to verify the effectiveness of the isolation system, nonlinear static and dynamic analyses are performed. The analysis revealed that isolated building has lower base shear (approximately 1/4) against the non‐isolated structure.